A Needs Analysis of EFL Students’ Reading Strategies, Media Use, and Teaching Materials in English Essay Comprehension - Al Hakim, Luqman; Widyahening, Evy Tri (Universitas Pendidikan Mandalika, 2025)
Reading activities require supporting resources, namely strategies, media, materials, reading processes, and assessments so that students can read and contribute to the success of reading class learning outcomes. This research aims to determine the reading needs of 3rd semester students that are currently taking reading academic purposes course in the English Language Education study program at Universitas Slamet Riyadi, which consists of 30 students. The research method used is descriptive qualitative. This research was carried out from March 2024 to July 2024. The data collection methods used were observation and questionnaires. In analyzing the data, researchers used interactive analysis consisting of data display, data reduction, and drawing conclusions. The research results show that students' needs related to media, materials and reading methods are (1) students need reading media, both digital and print; (2) students need authentic scientific reading material and simplified results; and (3) students still adopt conventional reading methods; so it requires a method based on digital tools to help understand reading. Thus, it can be concluded that reading media, strategies, and materials are needed by college students to achieve learning purposes. This research implies that improvement in using reading strategies, media, and materials to fulfill the students’ needs is going to be implemented in the next semester. The needs of the students are essential to bridge and connect between pedagogical policy, ELT current trends, and the students’ needs to achieve learning outcomes.